A new extended Remkan distribution and its application to the cancer data - Anu, O.; Pandiyan, P. (Brazilian Journal of Biometrics, 2025)
A new two-parameter Remkan distribution is derived. In this study a new version of the length-biased Remkan distribution is discussed. Mathematical properties of the new distribution, including moments, moment-generating functions, shape, order statistics, Renyi entropy, and Bonferroni curves, have been proposed. Also discussed was the simulation study of the proposed distribution. The length-biased Remkan distribution in survival data is discussed on real lifetime data from engineering and medical science. Finally analyzed, a real-life data set is fitted and the fit has been found to be good.